STUDI IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MENJADI GURU SEKOLAH LUAR BIASA DI KOTA MEDAN - Purba, Syahfitri (Psychology Department Faculty of Psychology Universitas Medan Area, 2015)
This study aimed to identify the factors that influence the motivation to become a teacher of the exceptional school, by looking at the contribution of the six factors were obtained from the journal of research conducted by Aaron (2006) and Agustien (2009): patience, interest in teaching, love of children, helping others, needs (salary) and the science. This research was conducted in two Exceptional Schools in Medan with research subjects totaling 47 teachers. Based on linear regression analysis, the result of six factors, only five factors that contribute or influence the motivation to become a teacher SLB patience, interest in teaching, love children, helping others and the science, while one factor did not contribute. Based on the analysis F percent note that of the six factors, like helping others become factors that most influence the motivation to become a teacher SLB it can be seen from the 47 teachers, 45 teachers expressed appropriate, the next second factor most influencing factor is patience, which can views of 47 teachers, 42 teachers expressed agree, followed by factors like children with 42 teachers stating agree. Factor of interest taught by 39 teachers expressed agree, then factors in the science with 28 teachers expressed agree, and the latter factor needs (salary) with 18 teachers expressed agree.Keyword: motivation to became a teacher, exceptional school